Education and social justice in a digital age - Sutherland, Rosamund (Policy Press, 2014)
Rosamund Sutherland argues against a skills-based curriculum suggesting that, from a social justice perspective, the priority of schools should be to teach traditional subjects, such as mathematics and history, giving young people the formal knowledge they are not likely to learn outside school. She draws on the work of Michael Young, Lev Vygotsky, Amaryta Sen and David Olson in order to develop new theoretical and practical insights that offer ways of changing policy and practice to improve equality and life chances for young people